Hydrophysics: Water dynamics in soil profile - Rodrigues, Valdemir Antonio [UNESP]; Canales, Antonio Ruiz; Rezende, Marcos Antonio [UNESP]; Costa, Vladimir Eliodoro [UNESP] (My University, 2015)
On its different stages of growth, the vegetation shows the dynamic of the consumption of water from the soil by evapotranspiration. The remaining water is stored according to soil texture and, as time goes by, it reaches the groundwater table. The objective of this work is to study the relation between humidity, density, porosity and shrinkage of the floodplain soil and riparian vegetation and their ability to store water. For this purpose, two locations for every type of soils were evaluated. Both were placed at the Agronomy University (Faculdade de Ciências Agronômicas) in São Manuel, State of São Paulo, Brazil. The riparian stands soil had native vegetation, the floodplain soil was vegetated with Southern Cattail (Typha domingensis). In both places, soil samples were collected from several depths: 0, 30, 60 and 100 cm. Results show that lower soil density values (0.15 g/cm3) with organic texture and high porosities values (up to 86.2%) were found in samples with the highest organic material content in the floodplain soil. For this field experiment, flood plains soils (characterized as basin gley soils) presented high volumetric instability with a retratibility of 67.49% and higher water storage capacities compared to riparian stands soils (characterized as fluvic neosoils).
Keywords: Density; Porosity; Riparian jungle; Soil; Water